Cross and multiple herbicide resistance across Ukraine - Schwartau, V.; Mykhalska, L. (Quarantine and plant protection, 2023)
Goal. Identify resistance to herbicides in weed species on the crops of leading agricultural companies in the regions of Ukraine and identify ways to counteract the emergence of resistant weed biotypes. Methods. The research of herbicide effectiveness was carried out in production and vegetation experiments. Control plants were collected on non-arable land. Statistical analysis was performed using StatPlus software from AnalystSoft Inc. Results. Field and greenhouse studies in 2014—2023 identified herbicide resistance in highly damaging biotypes of monocotyledonous and dicotyledonous weed species in Ukraine. In 2022—2023, herbicide-resistant ragweed (Ambrosia artemisiifolia L.) affected sunflower crops, the main crop that ensures the profitability of crop production in the country. Imidazolinone resistance in Ambrosia was identified in 2015. In 2023, multiply resistance to herbicides — acetolactate synthase inhibitors and protoporphyrinogen oxidase inhibitors (ALS+PРO) — was identified in A. artemisiifolia in large areas of sunflower in central and southern Ukraine. In previous years, resistant to the action of herbicides — acetolactate synthase inhibitors of the imidazolinone class ‒ imazapyr and imazamox biotypes of monocot Echinochloa crus-galli var. crus-galli (L.) P. Beauv., and dicot Amaranthus retroflexus L., and Chenopodium album L. have been identified. Cross-resistance to herbicides: monocot to sulfonylurea (nicosulfuron), and triazole pyrimidines (penoxsulam); dicots to sulfonylurea foramsulfuron, iodosulfuron-methyl-sodium, thifensulfuron-methyl, tribenuron-methyl; to sulfonylaminocarbonyl triazolinone derivative — thiencarbazone-methyl; to triazole pyrimidine derivatives — florasulam, and flumetsulam were established. The multiple resistance of Echinochloa crus-galli, Amaranthus retroflexus, and Chenopodium album to herbicides of the classes of glycine derivatives — glyphosate, monocot to graminicide pinoxaden, and dicot species to phenoxy carboxylic derivatives — 2.4-D, benzoic acid — dicamba; triketones — topramezone; diphenyl ethers — aclonifen have not been established. It was shown that herbicide compositions under the influence of the ammonium pool can increase the level of controlling resistant weed biotypes effectiveness. In 2018—2021, in rice crop rotations in the South of Kherson region, the emergence and spread of a cereal multiply resistant (ALS + ACC) species, Eragrostis spp. was detected. Conclusions. The identification of highly harmful resistant Ambrosia artemisiifolia, Echinochloa crus-galli, Amaranthus retroflexus, Chenopodium album, and Eragrostis spp. in the South and Central part of the «grain belt» of Ukraine shows the limited effectiveness of weed control exclusively with herbicides with one mechanism of action and requires a significant revision of the principles of crop rotation formation and methods of weed control in the state to maintain high levels of profitability and productivity of agrophytocenoses. Solving these issues is urgent in order to preserve Ukraine’s potential as one of the guarantors of world food security.